The early life growth of head circumference, weight, and height in infants with autism spectrum disorders: a systematic review - Roghayeh Molani-Gol; Mohammad Alizadeh; Sorayya Kheirouri; Fatemeh Hamedi-Kalajahi (BMC, 2023)
Abstract Backgrounds The Autism spectrum disorder (ASD) prevalence has increased significantly over the past two decades. This review summarizes the current knowledge of the association between the early life growth of head circumference (HC), weight, and height with ASD in infants. Methods PubMed, Scopus, Science Direct, and Google Scholar databases were searched up to November 2021 using relevant keywords. All original articles are written in English evaluating the early life growth of HC, weight, and height in infants with ASD were eligible for the present review. Results Totally, 23 articles involving 4959 infants were included in this review. Of 13 studies that evaluated HC of infants at birth, 10 studies (83.33%) showed that the HC at the birth of autistic children was similar to that of the average found in the control group. Among 21 studies that evaluated the HC and weight status in infants, 19 studies (90.47%) showed that autistic children had larger HC and weight than the control group or abnormal acceleration of head growth during infancy. Height growth of infants was investigated in 13 studies, of which 10 cases (76.92%) reported that infants with ASD were significantly longer than control groups. Most of he included studies had a good quality. Conclusions The findings suggest that in infants with ASD, without the contribution of birth growth factors and sex of the child, the growth of HC, weight, and height probably was faster than in infants with normal development, in early life. Therefore, these measurements might be useful as initial predictive biomarkers for the risk of developing ASD.